Aluminum Wastes Effect on Solar Distillation - Bellila, Abdelkader; Khechekhouche, Abderrahmane; Kermerchou, Imad; Sadoun, Ali; Siqueira, Antonio Marcos de Oliveira; Smakdji, Nafila (Bumi Publikasi Nusantara, 2022)
Aluminum wastes are widespread in the El Oued region of south-eastern Algeria, particularly in Aluminium workshops and factories. Because aluminum has a high heat conductivity, it can be used to increase the performance of solar stills. Two comparable solar stills were tested for this; one was used as reference solar still SSR, while the other contained Aluminium waste and was used as a modified solar still SSM. When compared to the reference still SSR, the results demonstrate that there is a 33.72 % improvement.